Pre- and postoperative chemotherapy in localized extremity soft tissue sarcoma: a European organization for research and treatment of cancer expert survey - Rothermundt, Christian; Kasper, Bernd (The oncologist, 2018)
Background The management of localized extremity soft tissue sarcomas (STS) is challenging and the role of pre- and postoperative chemotherapy is unclear and debated among experts. Materials and Methods Medical oncology experts of the European Organization for Research and Treatment of Cancer Soft Tissue and Bone Sarcoma Group were asked to participate in this survey on the use of pre- and postoperative chemotherapy in STS. Experts from 12 centers in Belgium, France, Germany, Great Britain, Italy, Switzerland, and The Netherlands agreed to participate and provided their treatment algorithm. Answers were converted into decision trees based on the objective consensus methodology. The decision trees were used as a basis to identify consensus and discrepancies. Results Several criteria used for decision-making in extremity STS were identified: chemosensitivity, fitness, grading, location, and size. In addition, resectability and resection status were relevant in the pre- and postoperative setting, respectively. Preoperative chemotherapy is considered in most centers for marginally resectable tumors only. Yet, in some centers, neoadjuvant chemotherapy is used routinely and partially combined with hyperthermia. Although most centers do not recommend postoperative chemotherapy, some offer this treatment on a regular basis. Radiotherapy is an undisputed treatment modality in extremity STS. Conclusion Due to lacking evidence on the utility of pre- and postoperative chemotherapy in localized extremity STS, treatment strategies vary considerably among European experts. The majority recommended neoadjuvant chemotherapy for marginally resectable grade 2-3 tumors; the majority did not recommend postoperative chemotherapy in any setting. Implications for Practice The management of localized extremity soft tissue sarcomas (STS) is challenging and the role of pre- and postoperative chemotherapy is unclear and debated among experts. This study analyzed the decision-making process among 12 European experts on systemic therapy for STS. A wide range of recommendations among experts regarding the use of perioperative chemotherapy was discovered. Discrepancies in the use of decision criteria were also uncovered, including the definition of what constitutes high-risk cancer, which is a basis for many to recommend chemotherapy. Before any standardization is possible, a common use of decision criteria is necessary.
Gesehen am 01.09.2020
First published: 30 November 2017